Interdisciplinarity and Career Training: Introduction to a Special Collection on the Discipline of Family Science. - Dyer, Kathleen D. (Marriage & Family Review)
The article discusses the academic discipline of family science within higher education. It explores the challenges of defining the disciplinary identity of family science due to its interdisciplinary nature and historical roots in various related fields. The collection of papers in the article highlights the need for further research on the history, student demographics, curriculum, and outcomes of family science programs to enhance the discipline's contribution to society. The papers also address the tension between career training and liberal arts education in family science programs, emphasizing the importance of empirical self-reflection to maintain the discipline's health and vibrancy.